Three roads to Rome? Comparative policy analysis of predictive tools in child protection services in Aotearoa New Zealand, England, & Denmark. Issue 3 (3rd July 2022) - Jørgensen, Andreas Møller; Webb, Calum; Keddell, Emily; Ballantyne, Neil
ABSTRACT: Across nation states, social work services have developed and implemented predictive assessment tools that utilize algorithms to calculate risk from large inter-linked databases. In this paper, we explore and compare the policy contexts for predictive tools in family and child protection services in England, Denmark and Aotearoa New Zealand. The development of predictive tools is part of a dynamic process of datafication triggering a range of political and professional conflicts involving political ideologies, policy orientations, ethical considerations, implementation techniques and tools for problem solving. Focusing especially on political and policy environments, we explore how predictive tools are discursively constructed and are promoted or challenged by key stakeholders. Claims-making regarding efficiency, accuracy, ethics, the role of the state and the causes of social problems play out differently in different policy contexts. Each case study provides insight into the processes assembling the use of predictive tools in child protection services. In Aotearoa New Zealand, key figures are embedded in central government and the public debates are closely tied to political actors and political ideologies. In comparison, in England and Denmark debates and actions are diffuse across levels of government and private and public sectors. In each case, some constant drivers closely linked to conceptions of the ideal state are identifiable.